Matrix Representations of Finite p-Groups over Commutative Local Rings of Characteristic p^s - Gudivok, P. M.; Pogorilyak, E. Y. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We determine in what cases the problem of description of nonequivalent matrix representations of a finite p-group over a commutative local ring of characteristic p^s is wild.